Reduction of Glare Discomfort and Photostress Recovery Time Through the Use of a High-Energy Visible–Filtering Contact Lens. Issue 12 (7th December 2022) - Renzi-Hammond, Lisa M.; Buch, John; Xu, Jie; Hammond, Billy R.
Abstract : Objectives: Glare discomfort (GDC) is the slight pain (discomfort) that arises when exposed to light that exceeds one's adaptive state. Such light can also cause a temporary loss in visual function (photostress, PS). We tested the hypothesis that filtering with a high-energy visible (HEV) light–filtering contact lens can reduce GDC and speed PS recovery time. Methods: Sixty-one subjects were randomized and fit with study lenses and 58 subjects completed as cohort (20–65 years of age). A double-masked, randomized, contralateral design was used (HEV filter on one eye; control lens on the other). Participants were given a 5-s exposure to a broadband white photostressor. Video images were analyzed, and palpebral fissure size during exposure was measured, as was PS recovery time to a 2-degree mid-wave target. Results: The HEV-filtering test lens was statistically superior ( P <0.0001) to the clear comparison contact lens with respect to the magnitude of squint (44.9% squint reduction) and photostress recovery time (24.3% faster recovery). Conclusions: High-energy visible light–filtering contacts can reduce GDC and speed PS recovery. Filtering HEV light before it is incident upon the retina is a natural strategy (e.g., by the lens and macular pigment) for attenuating some of the deleterious effects of bright broadband light.